﻿Teaching strategies for promoting students' self-regulated learning - Chi , Keung Cheng (Universiti Kebangsaan Malaysia, 2010)

(untitled)
﻿The article analyzes the relationship between learning performance and students ' self-regulation abiliq and discusses the teaching strategies aimed at enhancing students'self-regulationabilip. The theoretical framework in this article is based on the theories of self-regulated learning. Four dimensions that were studied include learning motivation, goal setting, action control, and learning strategies and conceptualized self-regulationability The researcher distributed questionnaires to the students in 20 subsidized secondary schools in Hong Kong. Through Factor Analysis, Validip Analysis and Multiple Linear Regression, it was found that studen6 'learning motivation; goal setting, action control, and leorning strategies were related significantly to their learning performances. Based on the findings, the researcher suggested that the teachers should guide students in conducting self-assessment, setting appropriate learning goals, and employing effective learning strategies in their learning.